Value creation and sport management - Gomez Lopez-Egea, Sandalio; Kase, Kimio, 1949-; Urrutia, Ignacio (Cambridge ; New York : Cambridge University Press, 2010)
'The sports business has become one of the fastest growing industries in recent years. Sports organizations now have the potential to generate massive amounts of revenue through a variety of different channels, including broadcasting rights, advertising and branding. However, the rise of sports-related business has so far received relatively little attention from management scholars and social scientists. This book argues that we can no longer afford to ignore this important economic and social phenomenon. It presents a new conceptual framework based on the concept of value creation to show how we can understand and explain the success and failure of sports organizations. Key concepts are illustrated with case studies of sporting organizations, including Real Madrid, FC Barcelona and the Americas Cup. Written by a team of authors from one of Spain's leading business schools, it provides a unique set of theoretical and practical insights for researchers and sports organization managers'--
1. The virtuous circle of value creation in the sports industry -- 2. Value creation and performance criteria for sport entities / Tanguy Jacopin, Kimio Kase and Ignacio Urrutia -- 3. National context and profit strategy of the sport entity : how to overcome the national borders of the sport entities? / Tanguy Jacopin -- 4. Value creation in two of the most prestigious Spanish football clubs : Real Madrid CF and FC Barcelona, 2000-2006 /Kimio Kase ... [et al.] -- 5. The proto-image of Real Madrid : implications for marketing and management / Kimio Kase, Ignacio Urrutia and Magdalena Opazo -- 6. Value creation from the organizational structure of a sports entity / Sandalio Gez, Carlos Martand Magdalena Opazo -- Appendix I. Why NGOs matter for the success of sporting events : the case of the America's Cup / Tanguy Jcopin and Ignacio Urritia -- Appendix II. Strategic evaluation of sponsorship and patronage / Kimio Kase, Ignacio Urrutia and Carlos Mart-- Appendix III. Structural characteristics of sport organizations : main trends in the academic discussion / Sandalio Gez, Magdalena Opazo and Carlos Mart
Includes bibliographical references and index.
Keywords: Professional sports -- Management; Professional sports -- Economic aspects; Sports administration